Photometry and calibration of Type Ia supernovae - Reis, Ribamar; Siffert, Beatriz (Cadernos de Astronomia, 2026)
Type Ia supernovae provided the first evidence, by the end of the 1990’s, that the expansion of the Universe is accelerated. Since then, various groups, using different observations have been confirmed this pioneer result, indicating that the Universe is in phase dominated by a cosmological constant, which is the simplest mechanism to explain the cosmic acceleration, in the context of general relativity. However, as the observation techniques were improving, the number of observed events increased to a point at the statistical uncertainties are not the biggest problem. The main focus of new projects shifted to controlling systematic errors due to modeling of the phenomenon, observation conditions e equipment limitations. In this work, we present a small glimpse of the photometry challenge, regarding the observation of astronomical events em large wavelenght bands and, from this information, infer intrinsic properties of such events. In addition, in briefly consider the challenge of controlling the propagation of uncertainties to the estimated distances e, consequently, to the cosmological parameters obtained from them.